"Autism is me": an investigation of how autistic individuals make sense of autism and stigma. Issue 3 (16th March 2022) - Botha, Monique; Dibb, Bridget; Frost, David M.
Abstract: There are many different perspectives for understanding autism. These perspectives may each convey different levels of stigma for autistic individuals. This qualitative study aimed to understand how autistic individuals make sense of their own autism and experience the stigma attached to autism. The study used critical grounded theory tools. Participants (N = 20) discussed autism as central to their identity, and integral to who they are. While participants thought of autism as value neutral, they expressed how society confers negative meanings onto autism, and thus, them. The findings also indicate that different understandings of autism confer different levels of stigma. Participants expressed constant exposure to stigma and managed this stigma in different ways. Such methods included reframing to more positive understandings of autism, the reclamation of language, and using concealment and disclosure strategically. The implications of these findings are discussed further in the article. Points of interest: Autistic research participants consider their autism to be value neutral – akin to any other feature like race or hair colour. Participants feel that society sees their autism as being a bad trait to have. Participants struggled with the tension in how they see themselves, versus how they believe society sees them. Participants are caught between disclosing that they are autistic and concealing it, but feel they are treated negatively either way. Participants use the word "autistic" to reclaim autism from stigma, and to reframe peoples understandings of autism to be less negative.